The Role of Interpersonal Communication and Work Motivation in Improving Employee Work Performance at PT PLN (PERSERO) UIP3BS UPT MEDAN - Evo Marisi Tumpal Damanik; Tonggo Sangap Timbul Girsang; Mery Suliyanti H. Sitanggang; Melky F. Simatupang (Journal of Management, Economic, and Accounting, 2025)
This study, titled "The Role of Interpersonal Communication and Work Motivation in Improving Employee Work Performance at PT PLN (Persero) UIP3BS UPT Medan," aims to determine the role of interpersonal communication and motivation on employee work performance. The research method used in this study is quantitative research with primary data sources. The results of this study indicate an F-calculated value of 55.564 at a significance level of α = 0.05. The F-table value obtained is 3.200, thus F-calculated > F-table (55.564 > 3.200) with a significance level (α) of 0.001 < 0.05. This means that it can be concluded that the variables of Interpersonal Communication (X1) and Motivation (X2) both have a simultaneous effect on Employee Work Performance at PT PLN (Persero) UIP3BS UPT Medan. Based on the coefficient of determination test, the combined influence of Interpersonal Communication (X1) and Motivation (X2) on Work Performance (Y) is 70.3%, while the remaining 29.7% is influenced by variables not detected in this research model. The conclusion of this study is that both interpersonal communication and work motivation simultaneously influence employee work performance at PT PLN (Persero) UIP3BS UPT Medan.